Real-Time Monitoring & Adaptive Protection of Power Transformer to Enhance Smart Grid Reliability - Raichura Maulik; Chothani N. G.; Patel Dharmesh (Electrical, Control and Communication Engineering)
Power transformer is one of the most important pieces of equipment in the grid to reliably and efficiently transmit power to the consumers. Asset management and protection are the best concepts for prolongation of transformer lifespan as well as for the increase of grid reliability. This article presents electrical and non-electrical parameter-based power transformer monitoring and protection. Various data such as core flux, age of asset, heat generation, current harmonics and temperature are monitored in real time and processed accordingly to enhance the working capability of the transformer. The proposed scheme is successfully tested on 15 kVA laboratory transformer using Arm CORTEX-M4 processor. A Fitness Function (Ff) is estimated from the collected data to examine the working condition of the transformer. Moreover, voltage, current and power-based inrush detection as well as Adaptive Power Differential Protection (APDP) are applied to protect the transformer against fault. The hardware implementation and result validation prove the effectiveness of the proposed scheme in enhancing reliability of the distribution grid.